Analisa Pengendalian Persediaan Bahan Baku Pakan Ternak dengan Metode Continuous Review dan Periodic Review di PT. XYZ - Dwi Sugiarti; Enny Aryanny (Universitas Batanghari Jambi, 2023)
PT. XYZ is a company that operates in the field of breeding chicken broilers produce products every day. In the production process of corn that is needed in the production of livestock feed this often experiences conditions of overstock and stock-out. This research aims to conduct control of the supply of raw materials for livestock feed in PT. XYZ by comparing the company method with the continuous review (Q) back order method and periodic review (P) back orders method so that the total cost of inventory is minimal. Based on the calculation with the company method obtained the total cost of inventory of Rp 60.220.905.000,- and the total minimum cost of stock obtainable by using the continuous review (Q) back order method of Rs 60.030.457.600. The forecast for corn demand from January 2023 to December 2023 was 12,900 tons. The company made the order amount of 685 Tons and reorder point of 106 Tons, so the total cost of inventory was Rp 60.698.546.500,-.